2016
DOI: 10.1080/01434632.2015.1127929
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual mothers’ language choice in child-directed speech: continuity and change

Abstract: An important aspect of Family Language Policy in bilingual families is parental language choice. Little is known about the continuity in parental language choice and the factors affecting it. This longitudinal study explores maternal language choice over time. Thirty-one bilingual mothers provided reports of what language(s) they spoke with their children. Mother-child interactions were videotaped when children were pre-verbal (5M), producing words in two languages (20M), and fluent speakers (53M). All childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 38 publications
(47 reference statements)
4
22
0
Order By: Relevance
“…Recent work suggests that mothers are fairly reliable in reporting which languages they themselves speak to their child (e.g. in short sessions: De Houwer & Bornstein, 2016). In a more comprehensive study, Marchman et al (2016) examined caregivers' accuracy in estimating their child's language experiences through daylong recordings.…”
Section: Accuracy and Reliability Of Language Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests that mothers are fairly reliable in reporting which languages they themselves speak to their child (e.g. in short sessions: De Houwer & Bornstein, 2016). In a more comprehensive study, Marchman et al (2016) examined caregivers' accuracy in estimating their child's language experiences through daylong recordings.…”
Section: Accuracy and Reliability Of Language Questionnairesmentioning
confidence: 99%
“…Only a handful of studies have addressed whether caregivers can accurately estimate their child's language experiences (De Houwer & Bornstein, 2016;Marchman et al, 2016). However, in these studies, the recordings were mostly conducted in one context (i.e.…”
Section: Research Questionsmentioning
confidence: 99%
“…A handful of studies have adopted a person-centered approach to investigate trajectories of mothers’ dual-language input to children. For instance, Dutch–French bilingual mothers’ dual-language input to their children was documented at infant ages 5, 20, and 53 months during spontaneous, non-structured interactions (De Houwer & Bornstein, 2016). At 5 months, most mothers used only one language with their children.…”
Section: Variability In Mothers’ Dual-language Input Over Timementioning
confidence: 99%
“…However, over half of the sample started using a second language when their children were 20 months of age, which might be driven by children’s emerging ability to speak the second language. At 53 months, many mothers switched back to the same single language they had used at 5 months, perhaps because children had become fluent speakers in that language (De Houwer & Bornstein, 2016). Another study with older children found that, from kindergarten to 8th grade, some mothers reported increasing in their use of English with their children during interactions at home; some used more home language; and some remained unchanged (Mancilla-Martinez & Kieffer, 2010).…”
Section: Variability In Mothers’ Dual-language Input Over Timementioning
confidence: 99%
“…Repeatedly using a language diary is likely to be more accurate (De Houwer, 2011). Actual recordings of CDS in bilingual families (De Houwer, 1997, 2014; De Houwer & Bornstein, 2016) are preferable, but require huge resources. It is in and through interaction, after all, that children hear language.…”
mentioning
confidence: 99%